Smart Grid Governance and Public Value Creation: A Policy Framework for Equitable Energy Transition in Urban Communities - Corinne Zylstra (Universitas Muhammadiyah Jakarta, 2024)
The transition toward low-carbon urban energy systems has increasingly positioned smart grids as strategic infrastructures for sustainability, efficiency, resilience, and public service innovation. However, the implementation of smart grids is not merely a technical matter of deploying sensors, smart meters, distributed energy resources, artificial intelligence, and digital control systems. It is also a governance challenge involving public legitimacy, institutional coordination, social equity, data protection, citizen participation, affordability, and the creation of public value. Many urban communities, particularly low-income and digitally marginalized groups, may experience the smart grid transition unevenly if policy design prioritizes technological optimization while neglecting distributional justice and procedural inclusion. This article develops a conceptual policy framework for smart grid governance that links electrical engineering innovation with public value creation and equitable energy transition. Using an integrative conceptual review, the study synthesizes literature on smart grid governance, energy justice, public value governance, smart city governance, and digital energy systems. The result is the proposed Equitable Smart Grid Public Value Framework, consisting of five interrelated governance pillars: equity-centered infrastructure planning, participatory energy governance, accountable data governance, adaptive regulatory capacity, and resilient public service delivery. The framework argues that smart grids should be governed not only as intelligent technical networks but also as public value infrastructures that must improve fairness, affordability, transparency, resilience, and citizen empowerment. The article contributes to interdisciplinary debate by integrating electrical engineering, public administration, energy policy, and urban governance perspectives. It also offers practical implications for local governments, utilities, regulators, and urban planners seeking to ensure that smart grid modernization supports a just and inclusive energy transition.